Outbreaks of Kingella kingae Infections in Daycare Facilities - Yagupsky, Pablo (Centers for Disease Control and Prevention, 2014)
During the past decade, transmission of the bacterium Kingella kingae has caused clusters of serious infections, including osteomyelitis, septic arthritis, bacteremia, endocarditis, and meningitis, among children in daycare centers in the United States, France, and Israel. These events have been characterized by high attack rates of disease and prevalence of the invasive strain among asymptomatic classmates of the respective index patients, suggesting that the causative organisms benefitted from enhanced colonization fitness, high transmissibility, and high virulence. After prophylactic antibacterial drugs were administered to close contacts of infected children, no further cases of disease were detected in the facilities, although test results showed that some children still carried the bacterium. Increased awareness of this public health problem and use of improved culture methods and sensitive nucleic acid amplification assays for detecting infected children and respiratory carriers are needed to identify and adequately investigate outbreaks of K. kingae disease.